Chicken soup for the college soul inspiring and humorous stories about college - Canfield, Jack; Universiti Teknologi Brunei; Canfield, Jack (Cos Cob, CT : Backlist, LLC, a unit of Chicken Soup for the Soul Publishing, 2012)
This latest helping of loving inspiration follows the millions of loyal readers of the Chicken Soup for the Teenage Soul series to the next stage of their lives, beyond adolescence and into young adulthood. Readers will love having this invaluable collection to guide, inspire, support, and encourage them throughout their college experience. If readers are devotees of the series, they will recognize this book as an instant source of strength and comfort; if this book is their introduction to the series, they will come to treasure it quickly. College is a time of excitement, exuberance, and triumph, as well as one of anxiety, doubt, and confusion. Readers will identify with the stories that express feelings they undoubtedly share as they stand at the brink of adulthood, sometimes ready to take the world by storm, other times wondering whether they will ever be ready. This book deals with the myriad issues of college life, from homesickness to partying to GPAs and everything in between. Whether freshmen, sophomores, juniors or seniors, this book is a must-read for all college students-as they'll be sure to agree. College graduates, too, will enjoy reminiscing about those unforgettable years as they read the stories in this collection. Chicken Soup for the College Soul is sure to be a hit with all readers.
Keywords: College students -- Conduct of life -- Anecdotes